PENGARUH INFLASI DAN NILAI TUKAR RUPIAH TERHADAP HARGA SAHAM DI SEKTOR INDUSTRI BARANG KONSUMSI PADA INDEKS SAHAM SYARIAH INDONESIA (ISSI) TAHUN 2012-2016 - Dini Yuniarti; Erdah Litriani (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2017)
Sharia Securities are effects that do not conflict with the principles of sharia in the Capital Market. This study aims to reveal how the influence of inflation and the rupiah exchange rate against stock prices in the consumer goods industry sector on the index of sharia stock indonesia (ISSI). The object of this research is all syariah stock listed in indonesia syariah stock index (ISSI) in Indonesia Stock Exchange (BEI) consumer goods industry sector period 2012-2016. Sampling sample in this research using Purpose Sampling method based on data availability during the study period and data type is secondary data, while the analysis method used is multiple linear regression model with panel data. The results showed that the Inflation and Rupiah Exchange variables have an effect and significant to the stock price in the consumer goods industry sector in Indonesia Sharia stock index (ISSI) period 2012-2016.